2020
DOI: 10.3390/polym12112673
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Poly(Monomethyl Itaconate)/Few-Layer Functionalized Graphene Oxide/Lithium Ion Nanocomposites

Abstract: Poly(monomethyl itaconate) is outstanding because it is a glassy and dielectric polymer obtained from sustainable feedstock. Consequently, the study of the properties of its nanocomposites has gained importance. Herein, the electrical properties of nanocomposites based on poly(monomethyl itaconate) and functionalized few-layer graphene oxide (FGO) in the presence and absence of lithium ions (Li+) are studied. Not only did the electrical conductivities of the nanocomposites present values as high as 10−5 Scm−1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…It is possible to observe that the electrical conductivity of FKM obeys the Jonscher's power law (Equation ). σω=σ0+italicAωs where σ 0 corresponds to the D.C.‐conductivity of the sample; 𝐴𝜔 𝑠 is the pure dispersive component of the A.C.‐conductivity, being a power law in terms of angular frequency ω and exponent s (0 < s ≤ 1), which is the degree of interaction between mobile charges and the molecular environment around them. A is a constant associated with the polarizability strength 26 . In this respect, the electrical conductivity of the FKM showed a linear increase with the frequency, and the conductivity of 6.16 × 10 −11 S/cm, registered at 0.1 Hz (Table 6), which indicates the insulating characteristic of FKM, and this value is comparable to that reported in the literature 27 .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…It is possible to observe that the electrical conductivity of FKM obeys the Jonscher's power law (Equation ). σω=σ0+italicAωs where σ 0 corresponds to the D.C.‐conductivity of the sample; 𝐴𝜔 𝑠 is the pure dispersive component of the A.C.‐conductivity, being a power law in terms of angular frequency ω and exponent s (0 < s ≤ 1), which is the degree of interaction between mobile charges and the molecular environment around them. A is a constant associated with the polarizability strength 26 . In this respect, the electrical conductivity of the FKM showed a linear increase with the frequency, and the conductivity of 6.16 × 10 −11 S/cm, registered at 0.1 Hz (Table 6), which indicates the insulating characteristic of FKM, and this value is comparable to that reported in the literature 27 .…”
Section: Resultssupporting
confidence: 83%
“…A is a constant associated with the polarizability strength. 26 In this respect, the electrical conductivity of the FKM showed a linear increase with the frequency, and the conductivity of 6.16 Â 10 À11 S/cm, registered at 0.1 Hz (Table 6), which indicates the insulating characteristic of FKM, and this value is comparable to that reported in the literature. 27 In the case of the FKM/G composite, the electrical conductivity, registered at 0.1 Hz, reaches 3.36 Â 10 À6 S/cm, which corresponds to an increase of five orders of magnitude.…”
Section: Optical and Electric Properties Of Fkm Compositessupporting
confidence: 81%
“…It was observed that the electrical conductivity of PEI increased dramatically by adding 10 wt.% GO-g-PMMI/BTN+10 wt.% rGO (σ’ = 1 × 10 −5 S/cm, recorded at ν = 10 −1 Hz) followed by the nanocomposite filled with 10 wt.% rGO (σ’ = 1 × 10 −7 S/cm, recorded at ν = 10 −1 Hz), where in both cases the conductivity behavior was independent of the frequency. This indicates that the charge transport is favored by the presence of graphene material [ 33 ]. Contrary to the nanocomposite filled only with GO-g-PMMI/BTN, which presented an electrical conductivity close to the conductivity of the polymeric matrix (σ’ = 1 × 10 −15 S/cm, recorded at ν = 10 −1 Hz) and the behavior of its conductivity increased with increasing frequency (σ’ = 1 × 10 −8 S/cm, recorded at ν = 10 6 Hz).…”
Section: Resultsmentioning
confidence: 99%
“…As known, one of the most widely used nanomaterials as fillers is graphene, due to its diversity of properties, such as its high surface area of 2630 m 2 ·g −1 and high mechanical properties of 1300 GPa [ 6 ]. In this respect, the high surface area of graphene allows for use in a wide range of multiple purposes, such as elastomers, thermoplastic, sustainable glassy nanocomposites [ 7 , 8 , 9 ] as well as hydrogel-based nanocomposites for environmental remediation, heavy metal absorption, and waste treatment [ 10 , 11 , 12 ]. Moreover, the high surface area of graphene allows hosting on its surface different nanomaterials which specific properties, such as magnetic properties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%